1999
DOI: 10.1002/(sici)1098-2264(199908)25:4<399::aid-gcc14>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

β‐catenin accumulation and mutation of the CTNNB1 gene in hepatoblastoma

Abstract: Hepatoblastoma is a rare malignant tumor of the liver that occurs in children at an average age of 2 to 3 years. Epidemiologic studies have shown an increased frequency of this tumor type in families affected by adenomatous polyposis coli. In addition to the epidemiologic data, molecular genetic studies suggest that inactivation of the APC tumor suppressor may be involved in hepatoblastoma tumorigenesis. A major function of APC is the downregulation of beta-catenin, a transcription-activating protein with onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 0 publications
3
41
0
Order By: Relevance
“…5,26 The detection of b-catenin mutations and/or protein accumulation in the majority of our hepatoblastoma cases (15/21; 71%) confirms that Wnt signal activation is implicated in the pathogenesis of sporadic hepatoblastoma. [5][6][7] Our results are in agreement with the studies of Koch et al, 5,27 who detected b-catenin point mutations in 22 and 25% of their sporadic hepatoblastoma cases, while Taniguchi et al reported a slightly higher percentage (33%) of mutated cases. 28 As reported by Takayasu et al, 25 we observed that the hepatoblastoma cases with b-catenin protein accumulation were much more numerous than the cases with identified b-catenin mutations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…5,26 The detection of b-catenin mutations and/or protein accumulation in the majority of our hepatoblastoma cases (15/21; 71%) confirms that Wnt signal activation is implicated in the pathogenesis of sporadic hepatoblastoma. [5][6][7] Our results are in agreement with the studies of Koch et al, 5,27 who detected b-catenin point mutations in 22 and 25% of their sporadic hepatoblastoma cases, while Taniguchi et al reported a slightly higher percentage (33%) of mutated cases. 28 As reported by Takayasu et al, 25 we observed that the hepatoblastoma cases with b-catenin protein accumulation were much more numerous than the cases with identified b-catenin mutations.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, double-hit inactivation of the APC gene has been demonstrated in familial adenomatous polyposis-associated hepatoblastoma. [4][5][6][7][8] Furthermore, mutations affecting the phosphorylation sites encoded in exon 3 of b-catenin (a mutation hot-spot in several epithelial cancers) have been detected in sporadic hepatoblastoma, where APC mutations seem to be rare. [4][5][6][7][8] Somatic mutations in exons 5-8 of the p53 gene, which encode the DNA-binding region where cancer-associated mutations most frequently occur, [9][10][11] are strongly implicated in the progression of the common adult form of liver cancer, hepatocellular carcinoma.…”
mentioning
confidence: 99%
“…Involvement of the canonical and non-canonical Wnt pathway in liver oncogenesis has been described by various investigators [59][60][61][62][63][64][65][66][67]. One of the most frequently described mechanisms for activation of the canonical signaling pathway in HCC involves activation of β-catenin through mutations in the CTNNB1 gene.…”
Section: Disturbances In Wnt/β-catenin Pathway In Liver Carcinogenesismentioning
confidence: 99%
“…This is accompanied by overexpression/repression of other genes involved in transmission of signals to the cell nucleus, with the resulting intensification of proliferation, migration and cellular invasion. At the molecular level, a characteristic trait described in hepatocellular tumors involves nuclear or cytoplasmic accumulation of β-catenin, detected in a higher proportion of cells in cases of hepatoblastoma (50-80%) than in HCC (8-40%) [60,[62][63][64]68]. Taniguchi et al detected CTNNB1 mutations in 19% of HCC and in 70% of hepatoblastoma cases.…”
Section: Disturbances In Wnt/β-catenin Pathway In Liver Carcinogenesismentioning
confidence: 99%
“…Chromosomal variations occur frequently in HB, having been reported in up to 88% of cases in a genome profiling study. 16 The most likely candidate genes identified thus far are CTNNB1 (catenin, beta-1-catenin) 17 and insulin-like growth factor II (IGF2) tumour suppressor at locus 11p15. 18,19 In addition, more than 85% of HBs show accumulation of β-catenin which indicates an activated Wingless-type (Wnt) pathway.…”
Section: 15mentioning
confidence: 99%